Overcoming Dehumanization in Education: The Significance of a Love-Based Curriculum in Improving Student Learning Effectiveness - Hasanah, Aisyah Ramadhani; Gustina, G; Utami, Aisyah Putri; Bal'qis, Aisyah Shinta; Khairani, Arrahmi; Ramli, Syahrur (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
This study aims to analyze the significance of implementing a love-based curriculum as a solution to dehumanization in education, which is characterized by the dominance of a mechanistic paradigm, excessive standardization, and neglect of the social-emotional dimensions of students. The method used qualitative phenomenology with data collection through interviews, observations, and document analysis in three secondary schools in Central Java. The results of the study reveal that the pressure of a dense curriculum and standardized assessment system does reduce the space for empathic practices. However, the findings also show that the seeds of love-based practices that have emerged, such as emotional check-ins and collaborative projects, have positive implications in terms of increasing students' sense of security, courage in learning, and more optimal cognitive function. The discussion concludes that a love-based curriculum is not only ethical but also scientifically supported as a transformative approach to enhance the effectiveness of holistic learning.